History and development of the steam locomotive - Brown, Robert Henry (My University, 1898)
Introduction: In this brief history of the development of the locomotive, only a few of the most important points can be considered. Two hundred years ago, a harmless vapor arose with the morning sun, and floated away unheeded by all, except perhaps, the artist and poet. How is it today? From myriads of towering columns, o’er which the fierce fire king flings his mantle, gushes in mimic clouds the quick breath of our new born Titan.
Citation: Brown, Robert Henry. History and development of the steam locomotive. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: History; Locomotive; Vapor; Theses; Manuscripts (documents)